Quantitative characterization of the Antarctic ozone hole - Akagi, K.; Naganuma, H.; Shibata, S.; Matsubara, K.; Takao, T.; Sakoda, Y.; Ito, T.; Watanabe, Y. (1994)
The long-term evolution of the Antarctic ozone hole is studied based on the TOMS data and the JMA data-set of stratospheric temperature in relation with the possible role of polar stratospheric clouds (PSC's). The effective mass of depleted ozone in the ozone hole at its annual mature stage reached a historical maximum of 55 Mt in 1991, 4.3 times larger than in 1981. The ozone depletion rate during 30 days before the mature ozone hole does not show any appreciable long-term trend but the interannual fluctuations do, ranging from 0.169 to 0.689 Mt/day with the average of 0.419 Mt/day for the period of 1979 - 1991. The depleted ozone mass has the highest correlation with the region below 195 K on the 30 mb surface in June, whereas the ozone depletion rate correlates most strongly with that in August. The present result strongly suggests that the long-term evolution of the mature ozone hole is caused both by the interannual change of the latitudinal coverage of the early PSC's, which may control the latitude and date of initiation of ozone decrease, and by that of the spatial coverage of the mature PSC's which may control the ozone depletion rate in the Antarctic spring.